Burger’s Disease Dealt with Cannabis Therapy- A Case Study - Robinson, Dror; Yassin, Mustafa (Advancement and New Understanding in Medical Science Vol. 7, 2024)
The current case report describes regression of digital ischemia in Thromboangiitis obliterans patient following high-dose medical cannabis therapy (MCT). MCT therapy was instituted as a pain-mitigating treatment when the patient refused amputation due to ischemic and infected foot. Three years later the digital ischemia has resolved leaving minimal scarring. The mechanism of action might be related to the anti-tobacco use effects of MCT as well as the anti-inflammatory action of CBD. The current case report describes the use of high-dose cannabis (Medical Cannabis Therapy, MCT) as a therapy for severe Thromboangiitis obliterans and results three years later. A 59-year-old heavy smoking patient was admitted due to infected and ischemic foot. The results were considered indicative of Burger’s disease. Intravenous antibiotic therapy was begun for 4 days, with signs of worsening infection and progression of the erythema and edema up to the ankle. The patient returned to gainful employment after one year (gardening technician), his work includes a physical component requiring walking, and some ladder climbing. Further prospective clinical series is needed prior to performance of a formal randomized clinical trial of MCT in limb ischemia.